How self-governance willingness and participation efficacy shape residents’ satisfaction with urban public services: Evidence from neighborhood renewal in Hangzhou, China - Yan Sun; Wenjie Hu; Xinqu Xia (PLoS ONE, 2026)
Using an original survey of 2,202 households across 36 renewed neighborhoods in Hangzhou, China, this study examines how resident agency—operationalized as self-governance willingness and participation efficacy—shapes satisfaction with urban public services within a legally structured participatory governance context. To address endogeneity, we estimate two-stage least squares models with district and street fixed effects, instrumenting self-governance willingness with distance to the provincial government offices and participation efficacy with policy awareness and community involvement; instrument diagnostics indicate strong and valid instruments. In the second stage, both constructs are positively associated with satisfaction. Mediation analyses show that participation efficacy is associated with lower perceived disparities between renewed and newly built neighborhoods, and perceived disparities, in turn, are negatively related to satisfaction, consistent with partial mediation in which effective participatory channels translate engagement into experienced fairness. By contrast, self-governance willingness is positively related to disparity sensitivity, yielding a suppression pattern absent adequate institutional responsiveness. Results are robust to additive-index specifications and the original five-point outcome, and with significantly larger effects among low-income, urban-hukou, small-unit groups. The findings underscore the value of institutionalized, responsive participatory arrangements that align with resident preferences, clarify responsibility allocation, and sustain feedback loops to enhance procedural fairness and, in turn, satisfaction within legally structured neighborhood renewal.